2009
DOI: 10.1111/j.1556-4029.2009.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Trend of Deliberate Self‐Harm in Western Nepal

Abstract: Acts of deliberate self-harm (DSH) not only affect the people directly involved, but also have grave psychological and social impact on the family and community. In the present study, a cohort of 173 cases of DSH reported from April 2002 to March 2005 was retrospectively analyzed, by perusing the medicolegal register maintained by the Emergency Department at the Western Regional Hospital, Pokhara in the Western Development Region of Nepal. The data were entered and analyzed using SPSS Version 10.1. More than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…3 Studies of deliberate self harm in western Nepal, and another have also shown a high rate of attempted suicide in young people, especially those in the age range of 15-24 years, with the maximum number of patients falling within these age ranges. 13,14 In this study there were male to female ratio is 1:1 while Shakya, reported a female preponderance with a ratio of 2:5.…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies of deliberate self harm in western Nepal, and another have also shown a high rate of attempted suicide in young people, especially those in the age range of 15-24 years, with the maximum number of patients falling within these age ranges. 13,14 In this study there were male to female ratio is 1:1 while Shakya, reported a female preponderance with a ratio of 2:5.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the remoteness and inaccessibility for amenities such as education, healthcare and the potential for higher incomes. Finally, those living with an abusive husband are more likely to commit suicide [15][16].…”
Section: Key Findings Profile Of Sufferersmentioning
confidence: 99%
“…It is thought that one suicide substantially affects six people surrounding it [15]. Therefore it is important to consider the implications that the high rates of suicide in women of a reproductive age has on others.…”
Section: Effect On Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nepal it is women of a reproductive age that suffer the highest rates of suicide and mental health problems [20][21][22]. The number of suicides within this group has increased from 22 per 100,000 in 1998 to 28 per 100,000 in 2008 [23].…”
mentioning
confidence: 99%